Uji Kisaran Inang Penyakit Downy Mildew (Pseudoperonospora cubensis) dan Antraknosa (Colletotrichum Sp.) pada Beberapa Tanaman Cucurbitaceae - Erise Anggraini; A. Muslim; Azizah Zuriana; Chandra Irsan; Bambang Gunawan (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2018)
Anggraini et al, 2018. Host-Range Analysis of Downy Mildew (Pseudoperonospora cubensis) and Anthracnose (Colletotrichum Sp.) on some Cucurbitaceae Plants. JLSO 7(2):213-224.Â Inhibiting factors of cucumber cultivation is Downy mildew disease that is caused by Pseudoperonospora cubensis and Anthracnose by Colletotrichum sp. The objective of this research was to observe pathogenicity of activity caused by Pseudoperonospora cubensis and Colletotrichum sp. isolated from cucumber towards Cucurbitaceae plants. The research was conducted at greenhouse and Phytopathology Laboratory, Department of Plant Pests and Diseases Faculty of Agriculture, University of Sriwijaya in September to December 2016. This study used Randomized Block Design (RBD), with four types of plants, 2 treatments and 4 replications. The results showed that the incubation period of the plant inoculation Downy mildew by Pseudoperonospora cubensis range between 4.5-5.0 days. Result of broadest spot area was on melon leaf 2.05 cm2 with the chlorophyll content of 0.4928 mg/g and the lowest result was on cucumber leaf 0.90 cm with the chlorophyll content of 0.7628 mg/g. While the results showed that the incubation period of the applied plant pathogen Colletotrichum sp. ranging from 3.0-4.5 days. Result of broadest spot area was on melon leaf 4.00 cm2 with the chlorophyll content of 0.3932 mg/g and the lowest result was on cucumber leaf 2.42 cm2 with the chlorophyll content of 0.7588 mg/g.